Nutritional, bioactive components and health properties of the milpa triad system seeds (corn, common bean and pumpkin) - Sánchez-Velázquez, Oscar Abel; Luna-Vital, Diego Armando; Morales-Hernandez, Norma; Contreras, Jonhatan; Villaseñor-Tapia, Elda Cristina; Fragoso-Medina, Jorge Alberto; Mojica, Luis (Frontiers in Nutrition, 2023)
The milpa system is a biocultural polyculture technique. Heritage of Mesoamerican civilizations that offers a wide variety of plants for food purposes. Corn, common beans, and pumpkins are the main crops in this agroecosystem, which are important for people's nutritional and food security. Moreover, milpa system seeds have great potential for preventing and ameliorating noncommunicable diseases, such as obesity, dyslipidemia, type 2 diabetes, among others. This work reviews and analyzes the nutritional and health benefits of milpa system seeds assessed by recent preclinical and clinical trials. Milpa seeds protein quality, vitamins and minerals, and phytochemical composition are also reviewed. Evidence suggests that regular consumption of milpa seeds combination could exert complementing effect to control nutritional deficiencies. Moreover, the combination of phytochemicals and nutritional components of the milpa seed could potentialize their individual health benefits. Milpa system seeds could be considered functional foods to fight nutritional deficiencies and prevent and control noncommunicable diseases.